2018
DOI: 10.21769/bioprotoc.2468
|View full text |Cite
|
Sign up to set email alerts
|

Buried Food-seeking Test for the Assessment of Olfactory Detection in Mice

Abstract: The sense of smell allows animals to discriminate a large number of volatile environmental chemicals. Such chemical signaling modulates the behavior of several species that depend on odorant compounds to locate food, recognize territory, predators, and toxic compounds. Olfaction also plays a role in mate choice, mother-infant recognition, and social interaction among members of a group. A key assay to assess the ability to smell odorants is the buried food-seeking test, which checks whether the food-deprived m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…To evaluate the impact of prolonged passive olfactory exposure on different aspects of olfaction, we initially performed the buried food test (Machado et al, 2018; Rattazzi et al, 2015; Yang & Crawley, 2009) that measures the animal's ability to locate a piece of food and its innate tendency towards foraging (Machado et al, 2018; Rattazzi et al, 2015; Yang & Crawley, 2009). We found that the latency to find the hidden food was similar between prolonged passive olfactory‐exposed animals (36.17 ± 11.70 s; n = 6; Figure 7a) and control non‐implanted animals (34.28 ± 11.83 s; n = 7; p > 0.05; Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the impact of prolonged passive olfactory exposure on different aspects of olfaction, we initially performed the buried food test (Machado et al, 2018; Rattazzi et al, 2015; Yang & Crawley, 2009) that measures the animal's ability to locate a piece of food and its innate tendency towards foraging (Machado et al, 2018; Rattazzi et al, 2015; Yang & Crawley, 2009). We found that the latency to find the hidden food was similar between prolonged passive olfactory‐exposed animals (36.17 ± 11.70 s; n = 6; Figure 7a) and control non‐implanted animals (34.28 ± 11.83 s; n = 7; p > 0.05; Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
“…The BFT was conducted to evaluate consciousness, attention, motivation, and organised thinking [42]. The procedure was carried out as described in the literature with some modifications [96]. Briefly, the rat was supplied one piece of sweetened cereal two days before the test.…”
Section: Buried Food Testmentioning
confidence: 99%
“…To detect behavioral olfactory deficits, we conducted two standardized buried food tests to optimize the detection of any anomalies in olfactory function in the early vs. late stages (46)(47)(48). Both tests determine the ability of mice to detect a food reward hidden in the bedding of clean housing cages.…”
Section: Buried Food Testsmentioning
confidence: 99%